Serum Prealbumin Concentrations, COVID-19 Severity, and Mortality: A Systematic Review and Meta-Analysis - Zinellu, Angelo; Mangoni, Arduino A. (Frontiers in Medicine, 2021)
Excessive inflammation and malnutrition are associated with coronavirus disease 2019 (COVID-19) severity and mortality. Combined biomarkers of malnutrition and inflammation, such as serum prealbumin, might be particularly attractive for early risk stratification. We conducted a systematic review and meta-analysis of studies reporting serum prealbumin in patients with COVID-19. We searched PubMed, Web of Science and Scopus, between January and November 2020, for studies reporting data on serum prealbumin, COVID-19 severity, defined as severe illness, prolonged viral load, receiving mechanical ventilation or admitted to intensive care unit (ICU), and mortality. Nineteen studies in 4,616 COVID-19 patients were included in the meta-analysis. Pooled results showed that serum prealbumin concentrations were significantly lower in patients with severe disease and non-survivors (standard mean difference, SMD, -0.92, 95% CI, -1.10 to -0.74, P<0.001). Extreme heterogeneity was observed (I2=77.9%; P<0.001). In sensitivity analysis, the effect size was not significantly affected when each study was in turn removed (range between -0.86 and -0.95). The Begg's (P=0.06) and Egger's t tests (P=0.26) did not show publication bias. Pooled SMD values were significantly and negatively associated with age (t=-2.18, P=0.045) and C-reactive protein (t=-3.85, P=0.002). In our meta-analysis, lower serum prealbumin concentrations were significantly associated with COVID-19 severity and mortality. This combined marker of malnutrition and inflammation might assist with early risk stratification and management in this group.